Tingkat Kesukaan dan Peningkatan Nilai Gizi Produk Meringue Lollipop dengan Penambahan Tepung Tulang Ikan Patin (Pangasius sp.): The Level of Acceptance and Increase in Nutrition for Meringue Lollipop Product with the Addition of Catfish Bone Meal (Pangasius sp.) - Ratnaningtyas, Susi; Anasri, Anasri; Niza, Aulia Ainun (Media Teknologi Hasil Perikanan, 2024)
The fishery processing industry result the by-products, such as in the form of fish bones, which can be processed into fish bone meal for fortification ingredient in food products. Catfish bone meal contains high calcium dan can be used to increase the mineral content of meringue lollipop. The purpose of this research is to understand the steps of the manufacturing process, hedonic level, chemical and microbiology content of meringue lollipop with the addition of catfish bone meal. The meringue lollipop was made using French method. There were 4 experimental group based on the addition of catfish bone meal, i.e. F0 (without catfish bone meal), F1 (5%), F2 (10%), and F3 (15%). The highest level of acceptance were obtained in F1 formulation with the addition of 5% catfish bone meal, with an appearance value of 7.28, aroma of 7.38, taste of 7.3, and texture of 6.88. The results of chemical tests for moisture content were 2.92% for F0 and 1.57% for F1, total ash content was 0.89% for F0 and 4.35% for F1, reducing sugar content was 0.315% for F0 and 0.31% for F1, protein content 11.82% for F0 and 12.71% for F1, calcium level 6.23 mg/100g for F0 and 1852.80 mg/100g for F1.